2020
DOI: 10.3389/fimmu.2020.611710
|View full text |Cite
|
Sign up to set email alerts
|

How to Combine the Two Landmark Treatment Methods—Allogeneic Hematopoietic Stem Cell Transplantation and Chimeric Antigen Receptor T Cell Therapy Together to Cure High-Risk B Cell Acute Lymphoblastic Leukemia?

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) has made tremendous progress in the last few decades and is increasingly being used worldwide. The success of haploidentical HSCT has made it possible to have “a donor for everyone”. Patients who received transplantation in remission may have a favorable outcome, while those who were transplanted in advanced stages of disease have a poor prognosis. Although chimeric antigen receptor T (CAR-T) cell therapy is currently a milestone in the immunothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 106 publications
2
14
0
Order By: Relevance
“…At present, there are an increasing number of clinical studies in this field. As more studies confirm the results, the clearance of MRD will greatly expand the application of CAR‐T cell therapy 36–38 . Regarding CIK cells, a recent Stanford University publication on 44 patients showed that early administration (day +21–35) of a single dose of allogeneic CIK cells (1 × 10 8 ) did not cause significant immunological complications 39,40 …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…At present, there are an increasing number of clinical studies in this field. As more studies confirm the results, the clearance of MRD will greatly expand the application of CAR‐T cell therapy 36–38 . Regarding CIK cells, a recent Stanford University publication on 44 patients showed that early administration (day +21–35) of a single dose of allogeneic CIK cells (1 × 10 8 ) did not cause significant immunological complications 39,40 …”
Section: Discussionmentioning
confidence: 86%
“…As more studies confirm the results, the clearance of MRD will greatly expand the application of CAR-T cell therapy. [36][37][38] Regarding CIK cells, a recent Stanford University publication on 44 patients showed that early administration (day +21-35) of a single dose of allogeneic CIK cells (1 × 10 8 ) did not cause significant immunological complications. 39,40 In conclusion, we were able to demonstrate how the combination of ATG-Cyclosporin-A and MTX together with the bone marrow as HSC source was associated with a high probability of survival after MMUD HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is another hotly debated topic. The combination of allo-HSCT and CAR-T therapy seem to provide benefit for patients with advanced diseases, particularly high-risk B-cell acute lymphoblastic leukemia (B-ALL) ( 42 ). However, the ideal application sequence of the two landmark therapies, the optimal therapeutic window for post allo-HSCT CAR-T infusion, the value of CAR-T in treating peri-transplantation minimal residual disease (MRD), and the utility of CAR-base technology in treating graft-versus-host disease (GVHD), the most frequent complication after allo-HSCT, remain unclear ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the most common application is CAR-T after the failure of an allo-HSCT, some studies are already testing CAR-T before transplantation as a bridge towards allo-HSCT. This strategy might allow an effective way to induce remission, reducing tumor burden, and therefore improving the outcome of the subsequent allo-HSCT [ 49 , 69 , 70 ]; however, CAR-T therapy is only at the beginning of its application, and many problems and difficulties are still avoiding its widespread application; standardization of the T-cell source to manufacture CAR-T is an active area of research that in the next few years will undoubtedly benefit the efficacy of CAR-T therapy.…”
Section: Future Perspectivementioning
confidence: 99%